Penile Agenesis: Demographic Characteristics and Management Experience in a Tertiary Care Teaching Hospital in Bangladesh (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Penile agenesis (aphallia) is an extremely rare congenital urogenital anomaly with an estimated incidence of approximately one in 30 million live births. It results from failure of development of the genital tubercle during embryogenesis leading to complete absence of the penis in a genetically male individual. Due to its rarity, clinical experience and management strategies are limited, particularly in developing countries. Methods: This retrospective observational study was conducted in the Department of Paediatric Surgery at Bangabandhu Sheikh Mujib Medical University (BSMMU) from January 2010 to December 2019. Medical records of patients diagnosed with penile agenesis were reviewed. Results: Seven patients were identified during the study period. Age at presentation ranged from 3 months to 6 years. All patients had a 46XY karyotype. Three patients had urethral opening in the perineum. Initial management in all cases consisted of cutaneous vesicostomy. Conclusion: Penile agenesis requires early diagnosis and multidisciplinary management. Vesicostomy provides effective initial urinary diversion and prevents upper urinary tract complications.Journal of Paediatric Surgeons of Bangladesh (2023) Vol. 14 (1 & 2): 36-38